Features of formation of students professional identity psychologists during training at university - Grinchencko, O. (НТУ "ХПИ", 2015)
The problem of self-determination of students-psychologists in pro-fessional sphere of life, which appears to them during education at the university. Objectified Cheney psychological and social components of this phenomenon and the role and importance of the learning process in its formation. The analysis of professional skills necessary for professional self-determination of students suggests that aspiration-opment attention to this problem will significantly increase the effectiveness of the shape-consciousness and development of the future professional.

В статье рассматривается проблема самоопределения студентов-психологов в профессиональной сфере жизни. Определены психологические и социальные составляющие самоопределения, а также роль и значение учебного процесса в его формировании. Проведенный анализ профессиональных качеств, необходимых для профессионального самоопределения студентов, позволяет сделать вывод о том, что усиление внимания к этой проблеме способно значительно повысить эффективность процесса формирования и развития самосознания будущего профессионала.
Особенности формирования профессионального самосознания студентов-психологов в период обучения в вузе
Keywords: professional self; identity; image professional; pedagogy; профессиональное самоопределение; самосознание; сферы деятельности; образ профессионала